Universiti Malaysia Pahang UMP Visit To MZR Global Sdn Bhd - UMP, PNC (MZR, 2023)
MZR Global Sdn Bhd was pleased to receive a courtesy visit from the Universiti Malaysia Pahang (UMP) team on the 9th of February 2023. A total of 8 representatives from UMP headedby Prof. Ts. Dr Kamal Zuhairi Zamli (Deputy Vice-Chancellorof Research & Innovation) graced the event where discussions and sharing of expertise regarding future collaborations took place.